COMMUNICATING WITH TARGET MARKET ENVIRONMENT - Đurić, Stanka (Journal of process management and new technologies, 2016)
The generally accepted definition that related to conceptual determination of market communication has not been performed. However, market communication can be defined as a set of activities and natural relationships that companies in various branches of authorities and business activities are established with other business organizations, and in order to establish a successful primary market communication, establishing a larger market share and the effective realization of the final goal, and certainly in market conditions that is profit. Activity which the company conducts are reduced to preparatory activities for the establishment of better relations with market operators, defining long-term strategies for successful business communication. The company has contact with their immediate environment, both internal and external. This, external environment emphasizing significantly because it consists of other economic organizations and entities, legal and regulatory bodies and consumers in order to take better starting position, preservation of the existing market share and also or extension thereof.